Pengaruh Return on Assets (ROA), Laba Kotor dan Risiko Investasi terhadap Expected Return Saham Perusahaan Manufaktur Sub Sektor Rokok Yang TerdaftarDi Bursa Efek Indonesia (BEI)Periode 2010-2014 - Gozali, Citra; Mary, Hilda (Jurnal Ekobistek, 2016)
Investor want to maximize the wealth would be interested in an investment can be expected to provide the level of common high control. By therefore, hearts take anyinvestment decisions, investors are always trying to minimize the different reviews on emerging risks, risks are good sort Term and long term risks character for companies and investors. The purpose of this research is to know the influence of the return on assets (ROA), gross profit and risk of investment to expected stock return on cigarette sector listing of manufacture companies in the Indonesian Stock Exchange (BEI) The sample of the research is determined by purposive sampling and it is consist of 3 companies on cigarette sector listing of manufacture companies in the Indonesian Stock Exchange (BEI) during period of 2010 to 2014.The analysis of this research uses the multiple linear regression analysis supported by SPSS version 21.0 for windows.The result of this research show that : 1). Partially the return on assets (ROA) had positive and significant influence to expected stock return, 2). Partially the gross profit had positive and no significant influence to expected stock return, 3). Partially the risk of investment had positive and significant influence to expected stock return, 4). Simultaneously the return on assets (ROA), gross profit and risk of investment had positive and significant influence to expected stock return. Keywords:Return On Assets (ROA), Gross Profit, Risk of Investment, Expected Stock Return.